Brewing a Sustainable Future: Exploring Standardisation and Cultural Diversity in Saudi Arabia and Indonesia's Specialty Coffee Industry through Indonesian Coffee Professionals' Lens - Kurniawan Arif Maspul (CV. Ulil Albab Corp, 2023)
This article offers a unique perspective on the specialty coffee industry by exploring the intersection of standardisation and cultural diversity in Saudi Arabia and Indonesia. It fills a gap in the existing literature by focusing on the experiences of Indonesian coffee professionals working in Saudi Arabia. This study's qualitative research includes interviews with Indonesian coffee professionals working in Saudi Arabia's growing cities, observations, and literature reviews. The research findings highlight the importance of balancing standardisation and cultural diversity in the specialty coffee industry. Indonesian coffee professionals recognise the significance of standardising specific parameters in the coffee brewing process to ensure consistency and quality while respecting consumers' cultural differences and preferences. The study's insights provide valuable guidance for coffee professionals, industry stakeholders, and policymakers interested in promoting a sustainable and diverse specialty coffee industry in the region. This article contributes to the growing literature on the intersection of coffee sociology, offering a fresh perspective on the complex relationships between culture, identity, and work practices in the coffee industry. Ultimately, this article aims to promote diversity, inclusivity, and sustainability in the specialty coffee industry, creating a more equitable and sustainable future for coffee professionals, consumers, and the environment.